2009
DOI: 10.3892/or_00000302
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of osteocalcin during the metastatic progression of prostate cancer

Abstract: Abstract. Osteocalcin expression is restricted to osteoblasts and serum osteocalcin level is elevated in metastatic bone tumors including prostate tumors, which predominantly metastasizes to the bone and causes typical osteoblastic lesions. Previously, we have reported that osteocalcin RNA is widely expressed but incompletely spliced in the prostate including prostate tumors. Considering that many studies using osteocalcin-driven gene therapy have been conducted to treat hormone refractory metastatic tumors, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A query in the current literature underscores the importance of an accurate regulation of osteocalcin and Gprc6a . Low levels of these two factors result in testicular insufficiency but high serum levels of osteocalcin (3032) as well as overexpression of Gprc6a (33) have been linked to the development of prostate cancer. Furthermore, knocking out Gprc6a using CRISPR/Cas9 technology abolished osteocalcin-mediated activation of ERK, AKT, mTOR signaling and cell proliferation in human prostate cancer xenograft models (34).…”
Section: Introductionmentioning
confidence: 99%
“…A query in the current literature underscores the importance of an accurate regulation of osteocalcin and Gprc6a . Low levels of these two factors result in testicular insufficiency but high serum levels of osteocalcin (3032) as well as overexpression of Gprc6a (33) have been linked to the development of prostate cancer. Furthermore, knocking out Gprc6a using CRISPR/Cas9 technology abolished osteocalcin-mediated activation of ERK, AKT, mTOR signaling and cell proliferation in human prostate cancer xenograft models (34).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that osteocalcin was decreased in NSCLC patients with bone metastasis [138,139]. In prostate cancer, some studies demonstrated significantly elevated osteocalcin levels in bone metastasis whereas other studies demonstrated no difference [140][141][142]. Taking into account its poor specificity, limited accuracy, and high biological variability, osteocalcin appears to be less than ideal for the diagnosis and prognosis of bone metastases.…”
Section: Osteocalcinmentioning
confidence: 99%
“…It is synthesized by osteoblasts during osteoid production and is later released into the bloodstream to promote bone growth [51]. Studies have shown that PCa BM patients exhibit higher OC levels [30,47,52], since osteoblasts' synthesis of OC is very closely tied to the progression of PCa metastasis [52,53]. Thus, elevated serum OC levels are regarded as signs of metastatic disease for PCa.…”
Section: Osteocalcin (Oc)mentioning
confidence: 99%